Maternity care models in a remote and rural network: assessing clinical appropriateness and outcome indicators. Issue 2 (29th March 2010) - Tucker, J; McVicar, A; Pitchforth, E; Farmer, J; Bryers, H
Abstract : Background: Little is known about performance of small rural maternity units, including stand-alone midwife units. Aim: To describe the proportions of women delivering locally, clinical appropriateness of model of care at delivery and outcome indicators for three rural staffing models of care. Design: Case note review. Setting: Remote and rural maternity units in NHS North of Scotland Region. Subjects and methods: 1400 deliveries to women from the catchments of eight rural units (stratified by staffing model) included those in local rural units and in associated distant referral units. Descriptive analysis examined women's risk, clinical appropriateness of model of care at delivery and outcomes aggregated by local catchment unit type and delivery unit type. Results: Local deliveries by staffing model were 31% (214/697) in midwife stand-alone units, 70% (236/336) in midwife units alongside non-obstetric medical support and 86% (317/367) in small obstetric-led units. Model of care at delivery was generally appropriate according to risk. Judged inappropriate were 3% (22/696) of women with complications delivering in midwife stand-alone units; and of referral unit deliveries, 6% (37/632) with suspected complications unconfirmed, plus 5% (31/633) discharged undelivered by referral hospital at >36 weeks' gestation. Risk profiles of catchment samples were similar, but caesarean section rates appeared lower and neonatal unit admissions higher for women from stand-alone midwife units. Conclusions: Rural women were generally referred appropriately for specialist care. These stand-alone midwife units provided intrapartum care for approximately one-third of rural women who remained without complications. Further evidence is needed about outcomes by staffing models of care.